Influence of Electrode Distance on Electrical Energy Production of Microbial Fuel Cell using Tapioca Wastewater - Harimawan, Ardiyan; Devianto, Hary; Al-Aziz, Rd. Habib R. M. T.; Shofinita, Dian; Setiadi, Tjandra (Journal of Engineering and Technological Sciences, 2018)
Microbial fuel cell is one alternative technology that can be used to simultaneously solve problems related with wastewater production and energy demand. This study investigates the influence of electrode distance on power density in microbial fuel cell using tapioca wastewater. Graphite sheet without metal catalyst was used for both electrodes, separated by Nafion membranes. Four variations of electrode distance were used. MFC with highest electrode distance give the highest equilibrium OCV (676 mV), while the MFC with shortest electrode distance give the highest power density (7.74 mW/m2). EIS measurement suggested that the charge transfer resistance is dominant in all MFC configuration. Wastewater COD removal were in the range of 35-46 %, which were in accordance with the power density for all MFC.